Organic Solar Cells: On the Physical Origins of Charge Separation at Donor–Acceptor Interfaces in Organic Solar Cells: Energy Bending versus Energy Disorder (Adv. Theory Simul. 4/2020). Issue 4 (7th April 2020) - de Sousa, Leonardo Evaristo; Coropceanu, Veaceslav; da Silva Filho, Demétrio Antônio; Sini, Gjergji
Abstract : Research aimed at understanding charge separation at donor–acceptor interfaces in organic solar cells is presented by Gjergji Sini and co‐workers in article number 1900230 . The cover images shows a globe as a giant solar cell. The hexagons and circles on the surface represent different organic molecules (donor and acceptors) and h + and e − represent the holes and electrons. The color gradients show the energy bending at the interface as a driving force for charge separation.